Hepatoid carcinoma of the ovary - A case report and literature review - Ana Karla Uribe Rivera; M. Alvarez Larraondo; L. Taxa Rojas; M. Bravo Taxa; A. Zevallos Cardenas (Elsevier, 2020)
We present the case of a 27-year old female with an ovarian tumor and alpha-fetoprotein (AFP) of 1210 ng/m, a right salpingo-oophorectomy was performed and had conservative complementary staging by gynecologic oncologists. The histopathological report was primary hepatoid carcinoma of the ovary (HCO), clinical stage IA, complementary treatment was adjuvant chemotherapy with BEP and remains clinical, imaging and biochemically disease free in three years follow up.